Conceptual modeling of information systems - Olive, A. (Springer, 2007)
Olivé’s textbook explains in detail the principles of conceptual modeling independently from particular methods and languages and shows how to apply them in real-world projects. He covers all aspects of the engineering process from structural modeling over behavioral modeling to meta-modeling, and completes the presentation with an extensive case study based on the osCommerce system, an online store-management software program freely available under the GNU General Public License. His presentation is based on well-known industry standards like UML and OCL as a particular conceptual modeling language, yet also delivers the basics of the formal logical language background.